2021
DOI: 10.3389/fitd.2021.745104
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Sand Fly Bites of Infected BALB/c Mice Enhance the Development of Leishmania Lesions

Abstract: Sand fly saliva has considerable immunomodulatory effects on Leishmania infections in mammalian hosts. Studies on several Leishmania – sand fly - host combinations have demonstrated that co-inoculation with Leishmania parasites enhances pathogenicity, while pre-exposure of hosts to sand fly bites provides significant protection against infection. However, the third scenario, the effect of sand fly saliva on parasite development in hosts infected before exposure to sand flies, remains an understudied aspect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
3
3
0
Order By: Relevance
“…Interestingly, only lemmings used for xenodiagnoses developed pathological signs on the ears. This is consistent with results previously published by Vojtková et al (2021) (52) in BALB/c mice infected with L. major, showing that sand fly bites post infection enhance formation of skin lesions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, only lemmings used for xenodiagnoses developed pathological signs on the ears. This is consistent with results previously published by Vojtková et al (2021) (52) in BALB/c mice infected with L. major, showing that sand fly bites post infection enhance formation of skin lesions.…”
Section: Discussionsupporting
confidence: 93%
“…It would be interesting to perform long term experiments and observe dynamics of the infection in several time intervals. Interestingly, only animals exposed to sand flies remained infected, whereas no parasites were observed in other animals, which also supports the influence of sand fly bites on the course of infection (Vojtková et al 2020) (52).…”
Section: Discussionsupporting
confidence: 68%
“…Interestingly, only lemmings used for xenodiagnoses developed pathological signs on the ears. This is consistent with previously stated hypothesis of enhancing effect of sand fly bites to the course of infection by Vojtkova et al (2021), who observed significantly faster and to a larger size lesion development in L. major infected BALB/c mice exposed to repeated bites of P. dubosqci compared to the unexposed group of mice, and the tissue parasite load was higher in rodents exposed to repeated bites [55]. Also in hamster model, increased transmissibility of L. donovani was observed following multiple exposures of hamsters to Lutzomyia longipalpis bites [56].…”
Section: Phlebotomus Duboscqi Femalessupporting
confidence: 94%
“…major infected BALB/c mice exposed to repeated bites of P . dubosqci compared to the unexposed group of mice, and the tissue parasite load was higher in rodents exposed to repeated bites [ 55 ]. Also in hamster model, increased transmissibility of L .…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the forced feeding process egestes more bacteria than normal which should wait for more details in future studies. Moreover, studies on multiple Leishmania -sand fly-host combinations have uncovered that pre-exposure of hosts to sand fly bites confers significant protection against Leishmania infection [ 80 ]. In the distant years, this pre-immunity was attributed to at least 20 diverse salivary proteins with anti-hemostatic and anti-inflammatory properties [ 24 ], but studies in recent years have emphasized the role of bacteria transmitted along with saliva [ 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%